2004
DOI: 10.1007/s11892-004-0081-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of type 1 diabetes with anti-T-cell agents: From T-cell depletion to T-cell regulation

Abstract: Studies in animal models of type 1 diabetes had suggested that the disease was due to an immune-mediated destruction of insulin-producing cells. As this understanding was developed, clinical trials that were directed against T cells were begun, because these lymphocytes were thought to be the primary mediators of disease. Initial studies used broad-spectrum agents and showed general efficacy in either preventing the loss of insulin secretion or reducing the need for exogenous insulin. Although encouraging, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Large-scale clinical trials of daclizumab and mycophenolate mofetil (MMF) in new-onset T1D failed to preserve beta-cell function or prolong the honeymoon period [150]. Hering et al promoted the use of T cell-depletional or modulatory agents for their single-donor islet transplant series, and a large number of preclinical studies support their use as a means to facilitate autoimmune regulation and tolerance [35,[151][152][153][154][155][156][157][158]. Bellin et al analyzing the Minnesota and CITR islet data, found that T cell-depletional induction, especially in combination with tumor necrosis factor alpha (TNFalpha) blockade, provided the most durable 50% insulin independence rates at five years posttransplant [148].…”
Section: Induction Of Immunosuppressionmentioning
confidence: 99%
“…Large-scale clinical trials of daclizumab and mycophenolate mofetil (MMF) in new-onset T1D failed to preserve beta-cell function or prolong the honeymoon period [150]. Hering et al promoted the use of T cell-depletional or modulatory agents for their single-donor islet transplant series, and a large number of preclinical studies support their use as a means to facilitate autoimmune regulation and tolerance [35,[151][152][153][154][155][156][157][158]. Bellin et al analyzing the Minnesota and CITR islet data, found that T cell-depletional induction, especially in combination with tumor necrosis factor alpha (TNFalpha) blockade, provided the most durable 50% insulin independence rates at five years posttransplant [148].…”
Section: Induction Of Immunosuppressionmentioning
confidence: 99%
“…It has already been acknowledged that this period, when most subjects show reduced need for exogenous insulin, is an optimal time for immune intervention in human clinical trials for T1D [2,3,[16][17][18]. However, there are immunemodulating protocols in secondary prevention of T1D (see TRIALNET) that do not take the remission period into consideration, perhaps because of the difficulty in its definition.…”
Section: Discussionmentioning
confidence: 99%
“…During the period immediately after the onset of T1D, many individuals need a reduced dose of insulin than expected. This period (remission period, also known as the honeymoon period) has been acknowledged as an advantageous time for immune intervention [2,3]. However, not all subjects will go through this remission phase and some might experience it for a longer period of time than others.…”
Section: Introductionmentioning
confidence: 99%
“…In the AbATE (Autoimmunity-Blocking Antibody for Tolerance) trial, conducted by the Immune Tolerance Network, subjects with recent-onset T1D received two 14-day courses of therapy with teplizumab, and were evaluated after two years for preservation of plasma C-peptide, a surrogate for residual insulin-producing cells. The mechanism of action of teplizumab was initially thought to deplete T cells similar to other immunotherapies that target T cells, such as OKT3, thymoglobulin, and Campath (anti-CD52) [6]. More recently, we reported an increase in the frequency of circulating central memory CD8 T cells in clinical responders [7], and further investigation revealed that accumulation of partially exhausted CD8 T cells, characterized by co-expression of TIGIT and KLRG1 together with high levels of EOMES-associated gene networks, was associated with successful response to teplizumab therapy [8].…”
Section: Introductionmentioning
confidence: 99%